Kajian Sebaran Penutup Lahan dan Nilai Temperature Humidity Index (THI) Kampus Universitas Negeri Semarang (UNNES) - Rilo, Pambudi; Budi, Santoso Tjaturahono; Ananto, Aji (Geo-Image, 2018)
This research uses quantitative method. Data analysis used quantitative descriptive of land cover interpretation data, vegetation distribution, temperature measurement and air humidity and THI value. The results of the study showed that: 1) UNNES from the interpretation data of UNNES photographic image 2015 has an area of 586,060 m² with built land covering 206,179 m² (35.18%), a water body of 3,547 m² (0.61%), 68,460 m² (11.68%), and tree vegetation 307,874 m² with 273,228 m² (46.62%) of the tree vegetation including campus park and 34,646 m² (5,91%) of forest. 2) Average THI Campus UNNES ranged from 26,51-27,11. 3) The lowest average score of 26.51 included in the comfort category is found in Kebun Wisata Pendidikan, meanwhile the biggest THI value of 27.11 included in the partially uncomfortable category located at Simpang 7 UNNES. The land cover condition at Simpang 7 UNNES, which is dominated by hard surface (asphalt road) and become the main transportation access becomes the factor of high THI value at that location. UNNES as a conservation campus with the increasing number of students and facilities and infrastructure development is expected to maximize the existence of existing parks with various types of tree in order to create comfort in lecturing activities